2006
DOI: 10.1128/mcb.01817-05
|View full text |Cite
|
Sign up to set email alerts
|

A Nuclear Export Signal and Phosphorylation Regulate Dok1 Subcellular Localization and Functions

Abstract: Dok1 is believed to be a mainly cytoplasmic adaptor protein which down-regulates mitogen-activated protein kinase activation, inhibits cell proliferation and transformation, and promotes cell spreading and cell migration. Here we show that Dok1 shuttles between the nucleus and cytoplasm. Treatment of cells with leptomycin B (LMB), a specific inhibitor of the nuclear export signal (NES)-dependent receptor CRM1, causes nuclear accumulation of Dok1. We have identified a functional NES ( 348 LLKAKLTDPKED 359 ) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 56 publications
2
39
0
Order By: Relevance
“…A proportion of both proteins also localize in the nucleus [29], [44]. Others and we reported that BRK phosphorylates nuclear Sam68 and promotes its subcellular relocalization [29], [49].…”
Section: Discussionsupporting
confidence: 60%
“…A proportion of both proteins also localize in the nucleus [29], [44]. Others and we reported that BRK phosphorylates nuclear Sam68 and promotes its subcellular relocalization [29], [49].…”
Section: Discussionsupporting
confidence: 60%
“…Immunoprecipitation and immunoblotting were performed as previously described (46). Briefly, cells were lysed in a lysis buffer containing 50 mM Tris-Cl (pH 7.4), 0.5% Nonidet P-40, 150 mM NaCl, 2 mM EDTA, 3% glycerol, and a Halt protease and phosphatase inhibitor cocktail (Pierce Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence was performed as described previously, with minor modifications (46). Briefly, cells on cover slides were fixed in 4% formaldehyde at room temperature for 15 min and then permeabilized with 0.5% Triton X-100 in phosphate-buffered saline (PBS) for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Dok1 shuttles between the plasma membrane and the nucleus in response to mitogens (43), similar to MEK1, by means of a functional NES. When Dok1 is present, it may facilitate release of PPAR␥ from its sequestering proteins MEK1 and Cav1 and, upon binding to ligand, promote its nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%